Nonuniform molecular features of myelinating Schwann cells in models for CMT1: Distinct disease patterns are associated with NCAM and c‐Jun upregulation. Issue 5 (13th February 2014) - Klein, Dennis; Groh, Janos; Wettmarshausen, Jennifer; Martini, Rudolf
<x xml:space="preserve">Abstract</x> We investigated three models for Charcot–Marie–Tooth type 1 (CMT1) neuropathy, comprising mice lacking connexin 32 (Cx32def), mice with reduced myelin protein zero (P0) expression (P0het) and transgenic mouse mutants overexpressing peripheral myelin protein 22 (PMP22tg), with regard of the expression of the developmentally regulated molecules NCAM, L1, the low‐affinity NGF‐receptor p75 (p75NTR) and the transcription factor component c‐Jun. We found that all molecules were uniformly expressed by myelin deficient and supernumerary Schwann cells. The mutant myelinating Schwann cells of PMP22tg mice showed a robust NCAM‐immunoreactivity in Schmidt–Lanterman incisures (SLI) that accompanies other early onset abnormalities, such as the presence of supernumerary Schwann cells and impaired myelin formation in some fibers. In line with this, Cx32def and P0het mice, which represent demyelinating models, only rarely express NCAM in SLI. Surprisingly, c‐Jun immunoreactivity displayed a mosaic‐like pattern with mostly negative and some weakly or moderately positive nuclei both in myelinating Schwann cells and Remak cells of wildtype (wt), P0het and PMP22tg mice. However, c‐Jun expression was substantially upregulated in myelinating Schwann cells of Cx32def mice and spatially associated with axon perturbation, a typical predemyelinating feature of Cx32 deficiency. Additionally, c‐Jun upregulation was correlated with an elevated level of GDNF, possibly causally linked to the typical compensatory sprouting of axons in Cx32def mice and CMT1X patients. Our findings suggest that in myelinating Schwann cells of distinct models of CMT1, c‐Jun upregulation is a marker for predemyelinating axonal perturbation while myelin‐related NCAM expression is indicative for early Schwann cell abnormalities. GLIA 2014;62:736–750